Pengaruh Islamic Corporate Social Responsibility (ICSR) dan Kepatuhan Syariah Terhadap Kinerja Perbankan Syariah - Ghefira Nurfatimah; Sriwardany Sriwardany; Junita Putri Rajana Harahap; Ova Novi Irama (STIE Amkop Makassar, 2025)
This study aims to examine the effect of Islamic corporate social responsibility (ICSR) and sharia compliance on the performance of Islamic banking. Islamic banking companies listed on the Indonesia Stock Exchange (IDX Syariah) in 2021-2024. Measurement of Islamic corporate social responsibility is proxied by the Islamic social reporting index and sharia compliance is proxied by measuring the profit sharing ratio, zakat performance ratio. This research is a quantitative study. Determination of the sample using the purposive sampling method, the sample obtained was 10 Islamic banking companies in the 2021-2024 period so that 40 observation data were obtained. The data used are secondary data and the data analysis technique used is multiple linear regression (multiple linear regression method) by conducting a series of classical assumption tests to ensure the feasibility of the data. Data processing used in this study uses the help of SPSS software version 30. The results of this study indicate that Islamic corporate social responsibility has a positive and significant effect on the performance of Islamic banking, sharia compliance has a positive and significant effect on the performance of Islamic banking. Based on the simultaneous test (F test), it shows that all independent variables have a simultaneous or joint effect on the dependent variable.